Understanding influenza transmission, immunity and pandemic threats - Mathews, John D. (Influenza Other Respir Viruses, 2009)
Abstract  The current pandemic threat can be best understood within an ecological framework that takes account of the history of past pandemics caused by influenza A, the relationships between pandemic and seasonal spread of influenza viruses, and the importance of immunity and behavioural responses in human populations. Isolated populations without recent exposure to seasonal influenza seem more susceptible to new pandemic viruses, and much collateral evidence suggests that this is due to immunity directed against epitopes shared between pandemic and previously circulating strains of inter‐pandemic influenza A virus. In the highly connected modern world, most populations are regularly exposed to non‐pandemic viruses, which can even boost immunity without causing influenza symptoms. Such naturally‐induced immunity helps to explain the low attack‐rates of seasonal influenza, as well as the moderate attack‐rates in many urbanized populations affected by 1918–1919 and later pandemics. The effectiveness of immunity, even against seasonal influenza, diminishes over time because of antigenic drift in circulating viruses and waning of post‐exposure immune responses. Epidemiological evidence suggests that cross‐protection against a new pandemic strain could fade even faster. Nevertheless, partial protection, even of short duration, induced by prior seasonal influenza or vaccination against it, could provide important protection in the early stages of a new pandemic.